2009
DOI: 10.1088/0004-637x/700/1/559
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Flare Ribbons in Coronal Null-Point Topology

Abstract: Flare ribbons are commonly attributed to the low-altitude impact, along the footprints of separatrices or quasiseparatrix layers (QSLs), of particle beams accelerated through magnetic reconnection. If reconnection occurs at a three-dimensional coronal magnetic null point, the footprint of the dome-shaped fan surface would map a closed circular ribbon. This paper addresses the following issues: does the entire circular ribbon brighten simultaneously, as expected because all fan field lines pass through the null… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
437
4
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(490 citation statements)
references
References 57 publications
(101 reference statements)
44
437
4
5
Order By: Relevance
“…Sympathetic flares have been extensively reported and investigated in the past decades (e.g. Hanaoka, 1996;Lang & Willson, 1989;Masson et al, 2009;Wang & Liu, 2012;Deng et al, 2013;Sun et al, 2013;Yang et al, 2014;Liu et al, 2015a). The possible agents of energy transported from the source region of energy release to the remote footpoints are nonthermal electrons (Tang & Moore, 1982;Nakajima et al, 1985;Martin & Svestka, 1988), thermal conduction front (Rust et al, 1985;Bastian & Gary , 1992), shock waves (Machado et al , 1988), and reconnection outflows (Hanaoka, 1996;Nishio et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic flares have been extensively reported and investigated in the past decades (e.g. Hanaoka, 1996;Lang & Willson, 1989;Masson et al, 2009;Wang & Liu, 2012;Deng et al, 2013;Sun et al, 2013;Yang et al, 2014;Liu et al, 2015a). The possible agents of energy transported from the source region of energy release to the remote footpoints are nonthermal electrons (Tang & Moore, 1982;Nakajima et al, 1985;Martin & Svestka, 1988), thermal conduction front (Rust et al, 1985;Bastian & Gary , 1992), shock waves (Machado et al , 1988), and reconnection outflows (Hanaoka, 1996;Nishio et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These dynamics are highly reminiscent of the slipping reconnection (Aulanier et al 2006) observed by Masson et al (2009). Analyzing observations of a confined flare presenting a circular ribbon, Masson et al (2009) noted signatures of field lines reconnecting by following a sequential order along a preferential direction.…”
Section: Spatial Characteristicsmentioning
confidence: 84%
“…The authors deduced the magnetic configuration of the AR during the flare from a potential extrapolation and found that (i) the reconnection initially takes place for field lines closer to a coronal null point, and that (ii) it eventually progresses further toward the direction of this null point. Thus, Masson et al (2009) found that the evolution of the reconnection is induced by the asymmetric magnetic configuration.…”
Section: Spatial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational examples of nearly circular post-flare loops (e.g. Masson et al, 2009) use potential field extrapolations to map the loop locations to a local separatrix dome formed from the fan plane of an overlying coronal null. Baumann, Haugbølle, and Nordlund (2013) modelled a similar configuration using a novel combination of PIC and magnetohydrodynamic (MHD) approaches and revealed that the underlying particle acceleration was driven by direct acceleration from interaction with the local reconnection electric field.…”
Section: Comparison With Topological Reconnection Modelsmentioning
confidence: 99%